THE EFFECT OF SHORT-FORM VIDEOS IN SOCIAL MEDIA AMONG GENERATION Z IN THEIR CONSUMPTION TOWARDS LIVE SPORTS TV BROADCASTING - Fathin Al Ghazali, Muhammad
Short-form videos has already become mostly been applied in various social media platforms. A short-form video is a format that can be up to 3 minutes in length. It is an effective and engaging way for businesses to reach audiences. Such form also has attracted the Generation Z the most. Some kinds of product marketing use this interesting phenomenon, including the sport field, particularly live sports TV broadcasting. Furthermore, studies have shown that less young generation is watching live sports broadcasting with most preferring to consume their sports-related content through the videos from social media and highlights rather than watching a full live game of sports. It is an interesting challenge to get young viewers, especially Generation Z, to watch sport on television with their consumer base being the children of the “pay-per-view”. If the sports industry wants to attract and retain them as the viewers, the industry needs to work around some adjustments to suit them. This paper explores how the effect of short-form videos towards the interest of Generation Z to purchase live sports TV broadcasting. The data collection technique was conducted using online questionnaires among 219 respondents where 179 respondents are the Generation Z and the rest of it is millennials and X generation. Afterwards, the data were analyzed by conducting quantitative approach, through correlation coefficient and regression analysis. Moreover, each respondent is asked to define live sports broadcast in three words to identify what the most interesting things so the industries can adopt them in their marketing strategy. The result shows that, to some extent, there is a positive correlation between the effect of shortform video among Generation Z towards live sports broadcast consumption. There are some significant variables for each regression model, as indicated by the p-value < 0.05. The obtained model corresponds to the three research questions that want to be answered. Model 1 indicates that the short-form videos are one of the factors that affect the generation Z’s consumer behaviour. The cost to watch the live sports is still the main consideration for generation Z. Model 2 shows that some features of the packages such as price discount, highlight of the match, and interactive feature with the audience could make the Generation Z want to pay for that. Model 3 indicates that the future of live sports broadcast is determined by its live broadcast and interactive nature. The interesting finding is that although the attention span of generation Z is notoriously quite short, but from the result we can see that they still can tolerate with the longer-form video such as live sports broadcast. Another interesting finding is that only generation Z’s respondent who do not care about features when cost is the priority (either free or discounted price). Therefore, as the managerial implications, the live sports broadcaster should consider the package price more significant rather than the various features of the live sport package offered. Moreover, the next priority of live sports broadcaster should be the thought of what kind of interactive nature of the sports industry product to attract Generation Z towards subscription.